2013
DOI: 10.1371/journal.pone.0067893
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Organization of the Nanoscale Surface Structures of the Dragonfly Hemianax papuensis Wing Epicuticle

Abstract: The molecular organization of the epicuticle (the outermost layer) of insect wings is vital in the formation of the nanoscale surface patterns that are responsible for bestowing remarkable functional properties. Using a combination of spectroscopic and chromatographic techniques, including Synchrotron-sourced Fourier-transform infrared microspectroscopy (FTIR), x-ray photoelectron spectroscopy (XPS) depth profiling and gas chromatography-mass spectrometry (GCMS), we have identified the chemical components that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 75 publications
6
63
0
Order By: Relevance
“…The presence of C H stretching bands with a prevalence of methylene bands is an indication of the presence of long-chain aliphatic hydrocarbons. This is consistent with previous reports that highlighted the presence of cuticular waxes on the surface of dragonfly wings [26,27]. It can therefore be concluded that the key components of the Odonata wings are similar for all wing samples tested, highlighting that these have not essentially changed over the past 40 years.…”
Section: Surface Chemistrysupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of C H stretching bands with a prevalence of methylene bands is an indication of the presence of long-chain aliphatic hydrocarbons. This is consistent with previous reports that highlighted the presence of cuticular waxes on the surface of dragonfly wings [26,27]. It can therefore be concluded that the key components of the Odonata wings are similar for all wing samples tested, highlighting that these have not essentially changed over the past 40 years.…”
Section: Surface Chemistrysupporting
confidence: 92%
“…Previously published work has revealed that the fundamental components of the cuticular layer of dragonfly wings consists of peptide linked structural protein, chitin components that comprise the bulk of the wing membrane [26], and waxy components including long chain aliphatic hydrocarbons (C 14 -C 30 ) together with some carboxylic acids (palmitic acid and stearic acid). These components make up the outermost layer of the insect wing epicuticle [27]. These components contribute to not only the superhydrophobicity of the wing, but also to the hierarchical structure of the wing, which has been found to impart bactericidal properties to some wing surfaces [28].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 In follow-up studies, the nanopillars on the dragonfly wing were found to kill Gram-positive bacteria as well as yeast. 24,25 Similar nanopillars found on specially treated silicon wafers (black silicon) 26 had similar effects. According to these researchers, bacterial cells are killed on contact as they stretch over the pillars.…”
Section: Introductionmentioning
confidence: 62%
“…Such smaller, sharper nanopillars found on dragonfly wings and on black silicon have also been proven effective in killing Gram-positive bacteria and yeast cells. 24,26 …”
Section: B Nanotopographical Effects On Cell Morphologymentioning
confidence: 99%
“…This discovery drew more attention to the design and application of surface topography for antimicrobial purposes. In addition to cicada wings, dragonfly wings (nanowires) 169,170 and gecko feet (nano-scale spinule arrays with a submicron spacing) 171 also possess similar functions to kill bacteria. Reprinted with permission from reference 168.…”
Section: Surface Patterns In Naturementioning
confidence: 99%